A face-off between Smaug and Caspar modulates primordial germ cell count and identity in Drosophila embryos - Girish Deshpande; Subhradip Das; Adheena Elsa Roy; Girish S Ratnaparkhi (Fly)
Proper formation and specification of Primordial Germ Cells (PGCs) is of special significance as they gradually transform into Germline Stem Cells (GSCs) that are ultimately responsible for generating the gametes. Intriguingly, not only the PGCs constitute the only immortal cell type but several specific determinants also underlying PGC specification such as Vasa, Nanos and Germ-cell-less are conserved through evolution. In Drosophila melanogaster, PGC formation and specification depends on two independent factors, the maternally deposited specialized cytoplasm (or germ plasm) enriched in germline determinants, and the mechanisms that execute the even partitioning of these determinants between the daughter cells. Prior work has shown that Oskar protein is necessary and sufficient to assemble the functional germ plasm, whereas centrosomes associated with the nuclei that invade the germ plasm are responsible for its equitable distribution. Our recent data suggests that Caspar, the Drosophila orthologue of human Fas-associated factor-1 (FAF1) is a novel regulator that modulates both mechanisms that underlie the determination of PGC fate. Consistently, early blastoderm embryos derived from females compromised for caspar display reduced levels of Oskar and defective centrosomes.